Peningkatan Keberdayaan BUMDes dalam Menghasilkan Energi Terbarukan melalui Penerapan Genset Biogas di Desa Rek Kerrek, Pamekasan, Jawa Timur: Enhancing BUMDes Empowerment in Renewable Energy Production through the Implementation of a Biogas Generator Set in Rek Kerrek Village, Pamekasan, East Java - Khamdi Mubarok; Andrie Kisroh Sunyigono; Sri Ratna Triyasari; Nor Qomariyah; Teguh Prasetyo; Vedrik Ardika; Nurhadi Mulyono; Nanda Putri Zahra; Farid Wahyu Prabowo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Biogas produced from cattle manure is a renewable energy source with potential use as an alternative fuel. BUMDes Sejahtera in Rek Kerrek Village, Palengaan District, Pamekasan Regency, manages an average of 20–30 head of cattle and faces problems related to the accumulation of manure that has not been optimally managed, resulting in environmental pollution. This community service program aimed to process cattle manure into biogas and use it as fuel for a generator to produce electricity. The program was implemented using the Participatory Action Research (PAR) method, which emphasizes the active involvement of partners in all stages of the activities. The implementation stages included focus group discussions (FGDs), socialization, training, technology application, assistance, and evaluation. The technologies implemented consisted of a Sistema.bio biogas digester installation and a biogas-powered generator (biogenset) with a capacity of 2400 W, utilizing biogas as a substitute for fossil fuel in electricity generation. The results show increased empowerment of BUMDes partners in the production aspect through the utilization of biogas and bioslurry fertilizer as new products, as well as the conversion of biogas into electrical energy. From a management perspective, the program contributes to improving partners’ capacity to manage cattle manure and to operate and maintain the provided equipment. The impacts of this program include preventing environmental pollution, reducing fossil-based energy consumption, and enhancing the productivity and managerial capacity of BUMDes in a sustainable manner.